Justice Construction In Qur’an Perspective - K, Muh. Daming; Tangngareng, Tasmin; M, Zulkifli; Syukri, Suhartini; Halimang, St. (Advances in Social Sciences Research Journal, 2017)
This study aims to determine the construction of justice in Qur’an. It used normative approach (syar’i) and historical approach. It included into liybrary research. Data collected by quoting, adapting, analyzing using content analysis to the relevant literatures, reviewing and taking conclusion. The results showed that the construction of justice in Qur’an can be seen in the principles of justice, equality of justice without symbols, the principle of honesty, balance in life, and purity principle of intention that will provide a guarantee of peaceful feelings for all parties. Besides, the justice aspects, include of aspects of accounts payable recording by no cheating of each transactions, aspects of law enforcement which is a guarantee of the survival of the safe, moreover, there are aqidah and beliefs aspects, justice in polygamy, reconciliation, and restoring problems.